مناظرة "أبي حاتم السجستاني" و"التّوزي" دراسة حجاجية (Revue El-Wahat pour les Recherches et les Etudes, 2021)
The literary debate is a fine art worthy to have much more consideration in the modern time. It is an adequate way to express opinions and openly argue with each other without showing offense or deny each other’s views. Each arguer uses points of view and arguments relevant to the subject matter. The preeminent view  will then be admittedly recognised and approved by the other side. The debate between Abu Hatim al-Sajistani and Abdullah Al-Tawzi is one of the finest debates in the Arabic grammar, wherein the two parties used strong arguments supported by evidence. During the debate stages each one acknowledged the other’s arguments without prejudice or demeaning and replied to those arguments showing their lack of performance. Al-Tawzi finally approved what had been said by Abu Hatim Al-Sajistani. During the debate, the two parties showed high morals and did not injure each other. It was really a high-class debate respecting ethics and serving the theme of the debated matter Keywords: Debate - Hajjaj - Altozi - Abu Hatem - Paradise - Mahal